Neoliberalism 4.0: The Rise of Illiberal Capitalism; Comment on "How Neoliberalism Is Shaping the Supply of Unhealthy Commodities and What This Means for NCD Prevention" - Ronald Labonté (Kerman University of Medical Sciences, 2020)
Neoliberal logic and institutional lethargy may well explain part of the reason why governments pay little attention to how their economic and development policies negatively affect health outcomes associated with the global diffusion of unhealthy commodities. In calling attention to this the authors encourage health advocates to consider strategies other than just regulation to curb both the supply and demand for these commodities, by better understanding how neoliberal logic suffuses institutional regimes, and how it might be coopted to alternative ends. The argument is compelling as possible mid-level reform, but it omits the history of the development of neoliberalism, from its founding in liberal philosophy and ethics in the transition from feudalism to capitalism, to its hegemonic rise in global economics over the past four decades. This rise was as much due to elites (the 1% and now 0.001%) wanting to reverse the progressive compression in income and wealth distribution during the first three decades that followed World War Two. Through three phases of neoliberal policy (structural adjustment, financialization, austerity) wealth ceased trickling downwards, and spiralled upwards. Citizen discontent with stagnating or declining livelihoods became the fuel for illiberal leaders to take power in many countries, heralding a new, autocratic and nationalistic form of neoliberalism. With climate crises mounting and ecological limits rendering mid-level reform of coopting the neoliberal logic to incentivize production of healthier commodities, health advocates need to consider more profound idea of how to tame or erode (increasingly predatory) capitalism itself.